2018
DOI: 10.1093/fampra/cmy123
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain is associated with increased health care use among community-dwelling older adults in Brazil: the Pain in the Elderly (PAINEL) Study

Abstract: Background Chronic pain is known to increase health care use in high-income countries, but in Brazil, little is known. Objective To investigate the association between chronic pain and health care use among Brazilian older adults and explore the relationship between pain severity and health care use. Methods This cross-sectional study was derived from the pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…This increase in age has already been identified as a factor strongly associated with a higher prevalence of CP 18 , a fact reinforced by the studies included in the present review 20,24,32,[35][36][37] . The location chosen to collect the sample is also a determining factor for the prevalence of CP, and this was observed in the present study, since the data collected at the interviewees' homes showed a lower prevalence of chronic pain [16][17][18]21,23,25,27 than that of studies from online data collection 37 , or specialized health centers 22 .…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…This increase in age has already been identified as a factor strongly associated with a higher prevalence of CP 18 , a fact reinforced by the studies included in the present review 20,24,32,[35][36][37] . The location chosen to collect the sample is also a determining factor for the prevalence of CP, and this was observed in the present study, since the data collected at the interviewees' homes showed a lower prevalence of chronic pain [16][17][18]21,23,25,27 than that of studies from online data collection 37 , or specialized health centers 22 .…”
Section: Discussionsupporting
confidence: 54%
“…This fact can infer that the presence of CP is not directly associated with the economic context of each nation. Regarding gender, CP in Brazil predominated in females [15][16][17][18][19][20]22,23,[25][26][27][28][29][31][32][33][35][36][37]40,[43][44][45][46][47]49 , as well as in studies from other countries 50,[52][53][54][55][56] . Moreover, a large portion of the samples was composed of adults and elderly individuals, with CP being more prevalent among the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in mainland China (thereafter China), plenty of studies have primarily focused on general healthcare utilization in the total population or in old age population (Gong et al 2016;Li et al 2016;Zhang et al 2019), nonurgent emergency department visits (Jiang et al 2020), oral health services (Xu et al 2019), social services (Zhu 2015; see "Social Services Utilization"), respite services among caregivers of frail older adults (Sun et al 2020), and long-term care services (Fu et al 2017). In Brazil, the Andersen Model has been applied to dental services utilization (Herkrath et al 2020), doctor visits and hospitalization (Torres et al 2018), and use of prescription drugs (Viana et al 2015). Limpuangthip et al (2019) applied the Model to older Thai people in use of denture services.…”
Section: Applicationsmentioning
confidence: 99%